2001
DOI: 10.1023/a:1012563825191
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The dynamics of selenium content in the plasma, lymph, and myocardium and plasma antioxidant activity were studied in male NISAG (hereditary stress-induced arterial hypertension) and Wistar rats with acute myocardial infarction and during recovery. In NISAG rats the decrease in selenium content correlated with the decrease in antioxidant activity. This probably aggravates the symptoms of experimental myocardial infarction in animals with hereditary arterial hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 5 publications
1
8
0
Order By: Relevance
“…These values are on the same order as what Yu et al obtained by experimental measurement [11]. For SWCNT bundles, there have been theoretical estimates that in order to achieve load transfer so that the full bundle cross-section would be participating in bearing load up to the intrinsic SWCNT breaking strength (when loading has, for example, been applied only to those SWCNTs on the perimeter), the SWCNT contact length must be on the order of 10 to 120 microns [109,110]. This is much longer than the typical length of individual SWCNTs in such bundles [111,112], where mean length values on the order of a few hundred nanometers have been obtained.…”
Section: Strength Due To Interlayer Slidingsupporting
confidence: 66%
“…These values are on the same order as what Yu et al obtained by experimental measurement [11]. For SWCNT bundles, there have been theoretical estimates that in order to achieve load transfer so that the full bundle cross-section would be participating in bearing load up to the intrinsic SWCNT breaking strength (when loading has, for example, been applied only to those SWCNTs on the perimeter), the SWCNT contact length must be on the order of 10 to 120 microns [109,110]. This is much longer than the typical length of individual SWCNTs in such bundles [111,112], where mean length values on the order of a few hundred nanometers have been obtained.…”
Section: Strength Due To Interlayer Slidingsupporting
confidence: 66%
“…Similar findings were published by Loyke [36] in the serum of SHR rats compared to normotensive animals, suggesting different metabolism of the SHR rats. Yakobson et al [8] compared NISAG (hereditary stress-induced arterial hypertension) rats and Wistar rats with acute myocardial infarction and found that, during recovery, selenium content in the plasma and myocardium of NISAG rats was higher than in normotensive animals, most probably due to more intensive functioning of the antioxidant systems. Negative correlations between both systolic and diastolic blood pressure and serum selenium levels were observed by Telišman et al [37].…”
Section: Discussionmentioning
confidence: 99%
“…Selenium belongs to a group of trace elements that includes iron, copper, zinc, and manganese. They are essential components of enzymatic systems that can affect arterial hypertension and myocardial infarction [8, 9]. Other nutritional factors that affect blood pressure and cardio- and cerebrovascular diseases include sodium, potassium, calcium, magnesium, vitamins A, C, and E, and essential fatty acids [10].…”
Section: Introductionmentioning
confidence: 99%
“…The morbid growth of mineral deposits in human heart valves (calcification) can lead to loss of their functionality and, thus, is the first reason for valve replacement and the third leading cause of CVD [ 9 ]. It was also established that trace elements, in particular Fe, Cu, Zn, Mn and Se, can affect the course of arterial hypertension and myocardial infarction [ 10 ]. Several elements (Se, Cr, Cu, Mg, Zn, Li and V) are suspected of being involved in the genesis of arteriosclerotic heart disease [ 11 ].…”
Section: Introductionmentioning
confidence: 99%